An Investigation of the Impact of the EDM Parameters on the Process Characteristics of the A2 Tool Steel - Elias, Rasha Ramiz; Mahdi, Qussay Salah; Abdulrazaq, Mustafa Mohammed (Engineering, Technology & Applied Science Research, 2025)
The most popular nontraditional method for metal cutting is Electrical Discharge Machining (EDM), which offers advantages over conventional methods. The metal machining sector has benefited greatly from the increased accuracy and speed using EDM in both the subtractive and additive manufacturing processes. This study focused on examining the process parameters and their impact on the Tool Wear Rate (TWR), Material Removal Rate (MRR), and surface roughness (Ra) in the EDM of A2 Steel. The Taguchi's Design of Experiments (DOE) (L9) was adopted and machining experiments were performed at different levels of current, pulse-off time (Toff), and pulse-on time (Ton). Analysis of Variance (ANOVA) was used to analyze the experimental results to examine the process inputs and obtain performance measures that maximize the MRR and reduce the rates of TWR and Ra. All experiments were performed with a 2 mm depth cut. The results showed that the lowest Ra value was 2.604 at a current of 36 A, Ton of 250 µs, and Toff of 100 µs, whereas the highest MRR was 11.719 mm3/min at a current of 48 A, Ton of 250 µs, and Toff of 75 µs. The minimum TWR was 0.296 mm3/min at a current of 36 A, Ton of 200 µs, and Toff of 75 µs. According to the statistical analysis, the most significant element influencing both the multiple and individual responses was the current that maximized the MRR, Ra, and TWR. This improves the part quality and has favorable impacts on the productivity and sustainability of this process.